Improving a model of the hybrid photovoltaic system with a storage battery for local object’s self-consumption involving the setting of power consumed from the grid - Shavolkin, Olexander; Shvedchykova, Iryna; Lishchuk, Victoria; Stanovskyi, Yevhen (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is energy processes in a hybrid photovoltaic system with a storage battery for the needs of a local object involving the setting of power consumed from the network. The task addressed was to build a mathematical model of energy processes with the function of determining control parameters providing for the possibility of changing control scenarios. The mathematical model of the storage battery has been improved, taking into account the charge modes and discharge currents in terms of accuracy of reproduction of the manufacturer’s specification not worse than 3 %. A structure of the model was proposed with separation of module, which defines control parameters, as well as the schedule of power setting for selected scenarios. A variable is introduced into the model description, which determines the specified power value and ensures the construction of SoС(t) schedule. An additional mode to increase the energy use of the photovoltaic battery and restrictions on the measured value of load power were taken into account. Modeling with a change in time scale was proposed: first, control parameters are determined, followed by modeling in the daily cycle. This eliminates the need for preliminary calculations before modeling and provides the ability to verify the determination of system parameters with subsequent adjustment. A procedure for determining control parameters with power setting and adjusting the model under different control scenarios has been devised. When using archival generation data for the location of the facility, this makes it possible at the design stage to choose an option for implementing the power supply system with the desired indicators. For specific uses, it has been shown that underestimating the power of a photovoltaic battery by only 9 % increases energy costs by 1.72–1.39 times. Overstating power by 16.7 % impairs usage by 13.7 % while reducing costs by 1.4 % to 2.5 %